Turki, Hagia Sophia dan Kebangkitan Politik Islam: Membaca Fenomena Peralihan Museum Bersejarah Menjadi Masjid - Muhammad, Luthvi Nur (LoroNG: Media Pengkajian Sosial Budaya, 2020)
The city of Constantinople, or what is now known as Istanbul, was the capital of two great world civilizations, namely the Byzantine Empire and the Ottoman Empire. These civilizations left historical traces, one of which was the Hagia Sophia. On May 29, 1453, the city of Constantinople was conquered by Mehmet II, which became the beginning of a new civilization. Mehmet II created prestige and symbolic power on the Hagia Sophia building for his political interests in this conquest. This article will discuss the transition of the function of the Hagia Sophia. The research method used is a literature study. The results of this study are, Hagia Sophia has passed more than 15 centuries and is a silent witness to the ongoing transition of power in the land of Constantinople. In its history, Hagia Sophia has often been used as a symbol of the glory of its era. This article highlights the transition of the Hagia Sophia from a museum to a mosque which has received a response from the international community. This change is considered evidence of the rise of political Islam in Turkey under the leadership of President Erdogan. The political promise of Erdogan and his Islamist AKP Party is suspected to be the reason behind the change in the status and function of the Hagia Sophia. Amid various criticisms, both domestically and internationally, for this policy, the Erdogan government believes that the changes made are entirely Turkey’s constitutional rights that cannot be interfered with by anyone. Kota Konstatinopel atau yang saat ini disebut dengan Istanbul merupakan ibu kota dari dua peradaban besar dunia yaitu Kekaisaran Byzantium dan Kesultanan Ottoman. Kedua peradaban ini meninggalkan jejak sejarah, salah satunya yaitu Hagia Sophia. Pada 29 Mei 1453 Kota Konstatinopel ditaklukkan oleh Mehmet II yang menjadi awal dari sebuah peradaban baru. Dalam penaklukkan tersebut, Mehmet II menciptakan prestise dan kekuatan simbolis pada bangunan Hagia Sophia demi kepentingan politiknya. Artikel ini akan membahas mengenai fenomena peralihan fungsi Hagia Sophia. Metode penelitian yang digunakan yaitu studi pustaka. Hasil penelitian ini yaitu, Hagia Sophia telah melewati lebih dari 15 abad dan menjadi saksi bisu berlangsungnya transisi kekuasaan di tanah Konstantinopel. Dalam sejarahnya, Hagia Sophia seringkali dijadikan simbol kejayaan pada eranya. Artikel ini menyoroti peralihan Hagia Sophia dari museum ke masjid yang mendapatkan respon dari masyarakat internasional. Perubahan ini ditengarai menjadi bukti bangkitnya politik Islam di Turki dibawah kepemimpinan Presiden Erdogan. Janji Politik Erdogan dan Partai AKPnya –yang berhaluan Islamis- ditengarai menjadi alasan dibalik pergantian status dan fungsi Hagia Sophia tersebut. Ditengah berbagai kritik, baik dari dalam negeri maupun dunia internasional terhadap kebijakan ini, Pemerintahan Erdogan berasalan bahwa perubahan yang dilaku.